Oral Dexamethasone vs. Oral Prednisone for Children With Acute Asthma Exacerbations: A Systematic Review and Meta-Analysis - Wei, Jienan; Lu, Yan; Han, Fang; Zhang, Jing; Liu, Lan; Chen, Qingqing (Frontiers in Pediatrics, 2019)
Background: This systematic review and meta-analysis was conducted to compare relapse rates and adverse effects with oral dexamethasone vs oral prednisone for acute asthma exacerbations in pediatric patients. Methods: A computerized literature search of PubMed, Embase, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials) and Google scholar databases was carried out till 1st August 2019. Six Randomised controlled trials (RCTs) and 1 quasi-RCT were included. Dosage of dexamethasone and prednisone varied across studies. Studies were grouped based on the follow-up period and duration of dexamethasone administration. Results: There was no significant difference in the relapse rate between dexamethasone and prednisone at 1-5 days (RR 1.46, 95%CI 0.69-3.7, P= 0.32; I2=0%) and 10-15 days of follow up (RR 1.16, 95%CI 0.80-1.68, P= 0.44; I2=0%). Pooled analysis found no significant difference in relapse rates with 1-day (RR 1.15, 95%CI 0.68-1.95, P= 0.60; I2=0%) and 2-day dosage of dexamethasone (RR 1.25, 95%CI 0.82-1.92, P= 0.30; I2=0%) compared to prednisone. Hospital readmission rates after initial discharge were not significantly different between the two drugs (RR 1.49, 95%CI 0.56-4.01, P= 0.43; I2=0%). Frequency of vomiting at ED (RR 0.21, 95%CI 0.05-0.96, P= 0.04; I2=50%) and at home (RR 0.42, 95%CI 0.25-0.69, P= 0.0007; I2=0%) was significantly higher with prednisone as compared to dexamethasone. Conclusion: While our results indicate that both dexamethasone and prednisone have similar relapse rates when used for acute asthmatic exacerbations, strong conclusions cannot be drawn due to paucity of large scale RCTs and limited quality of evidence. Dexamethasone is however associated with lower incidence of vomiting as compared to prednisone. Further homogenous RCTs are needed to provide robust evidence on this topic.